Knowledge-Based Planning for Robustly Optimized Intensity-Modulated Proton Therapy of Head and Neck Cancer Patients - Xu, Yihang; Cyriac, Jonathan; De Ornelas, Mariluz; Bossart, Elizabeth; Padgett, Kyle; Butkus, Michael; Diwanji, Tejan; Samuels, Stuart; Samuels, Michael A.; Dogan, Nesrin (Frontiers in Oncology, 2021)
Purpose: To assess the performance of a proton-specific knowledge-based planning (KBP) model in creation of robustly optimized IMPT plans for treatment of advanced head and neck (HN) cancer patients. Methods: Seventy-three patients diagnosed with advanced HN cancer previously treated with Volumetric Modulated Arc Therapy (VMAT) were selected and replanned with robustly optimized Intensity Modulated Proton Therapy (IMPT). A proton specific KBP model, RapidPlanPT (RPP), was generated using fifty-three patients (twenty unilateral cases and thirty-three bilateral cases). The remaining twenty patients (ten unilateral and ten bilateral cases) were used for model validation. The model was validated by comparing the target coverage and OAR sparing in the RPP generated IMPT plans to that of the expert plans. To account for the robustness of the plan, all uncertainty scenarios were included in the analysis. Results: All the RPP plans generated were clinically acceptable. For unilateral cases, RPP plans had higher CTV_primary V100 (1.59% ± 1.24%) but higher homogeneity index (HI) (0.7 ± 0.73) compared to the expert plans. In addition, the RPP plans had better ipsilateral cochlea Dmean (-5.76Gy ± 6.11Gy), with marginal to no significant difference between RPP plans and expert plans for all other OAR dosimetric indices. For the bilateral cases, the V100 for all CTVs was higher for the RPP plans than for the expert plans, especially the CTV_primary V100 (5.08% ± 3.02%), with no significant difference in the HI. With respect to OAR sparing, RPP plans had a lower spinal cord Dmax (-5.74Gy ± 5.72Gy), lower cochlea Dmean (left: -6.05Gy ± 4.33Gy, right: -4.84Gy ± 4.66Gy), lower left and right parotid V20Gy (left: -6.45% ± 5.32%, right: -6.92% ± 3.45%), and a lower integral dose (-0.19Gy ± 0.19Gy). However, RPP plans increased the Dmax in the body outside of CTV (body-CTV) (1.2Gy ± 1.43Gy), indicating a slightly higher hotspot produced by the RPP plans. Conclusion: IMPT plans generated by a broad-scope RPP model have a quality that is, at minimum, comparable to, and at times superior to, the expert plans. The RPP plans demonstrated a greater robustness for CTV coverage and better sparing for several OARs.